Analitična mehanika - Ambrožič, Milan; Hölbl, Arbresha (University of Maribor Press, 2023)
Analytical Mechanics. In the course Analytical mechanics numerous problems in mechanics, particularly topics from dynamics, are treated in a more systematic way, as compared to ordinary physical problems, e.g., in relation to second Newton law. In this way, we can also include more complex geometries in the motion of bodies. The key part od analytical mechanics is introduction of generalized coordinates as independent variables of motion, used to express either Lagrange function or Hamiltonian. Finally, the corresponding differential equations must be solved in order to find the time development of generalized coordinates. Gravitation and oscillation are typical areas where the mathematical formalism of analytical mechanics can be used.